2021
DOI: 10.3390/antiox10091497
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in the Senescence Pattern of Auditory Cells in Age-Related Hearing Loss

Abstract: Age-related hearing loss (ARHL) is an increasing and gradual sensorineural hearing dysfunction. Oxidative stress is an essential factor in developing ARHL; additionally, premature senescence of auditory cells induced by oxidative stress can produce hearing loss. Hydrogen peroxide (H2O2) represents a method commonly used to generate cellular senescence in vitro. The objective of the present paper is to study H2O2-induced senescence patterns in three auditory cell lines (House Ear Institute-Organ of Corti 1, HEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…H 2 O 2 is the most common agent inducing senescence because it naturally induces oxidative stress, which can cause premature senescence in auditory cells, resulting in AHL [ 41 ]. The model of senescence induced by H 2 O 2 in the HEI-OC1 cell lines, can be a useful tool to study the intrinsic mechanisms responsible for AHL in vitro [ 42 ]. In this study, we found that REST knockdown by siRNA increases the expression of p53 and cleaved caspase-3 in HEI-OC1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is the most common agent inducing senescence because it naturally induces oxidative stress, which can cause premature senescence in auditory cells, resulting in AHL [ 41 ]. The model of senescence induced by H 2 O 2 in the HEI-OC1 cell lines, can be a useful tool to study the intrinsic mechanisms responsible for AHL in vitro [ 42 ]. In this study, we found that REST knockdown by siRNA increases the expression of p53 and cleaved caspase-3 in HEI-OC1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, all ototoxic drugs must cross the BLB to enter the inner ear tissues to exert their cytotoxic effects and induce hearing loss; therefore, extensive vacuolization in the SV has always been observed in related investigations. Moreover, the inner ear has been considered an immune-privileged site because of the presence of BLB (Rivas-Chacón et al, 2021). Autoimmune inner ear disease usually manifests as immunoglobulin G deposition in the SV.…”
Section: Discussionmentioning
confidence: 99%
“…Luz and Jiang conducted experiments in SV-k1 cell lines (from SV) and primary marginal cells of the SV, respectively (Jiang et al, 2018;Rivas-Chacón et al, 2021), to explore the oxidative stress mechanism in SV in ARHL. Recently, researchers have identified age-related changes in the morphology and number of macrophages in the human SV, and suggested that further investigations of the role of macrophage-associated inflammation in SV in ARHL are necessary (Noble et al, 2019).…”
Section: Alport Syndromementioning
confidence: 99%
“…However, multiple stressors can result in ROS overproduction and tissue accumulation [22,134] Accumulation of ROS and other free radicals can impair DNA and break down cellular proteins and lipids, contributing to apoptotic cell death in the cochlea [85]. OS also contributes to the cellular senescence pattern in the ageing cochlea [1]. Rivas-Chacon and colleagues reported that OS and premature senescence significantly impaired cell viability in three auditory cell lines (HEI-OC1, OC-k3, and SV-k1) [1].…”
Section: Oxidative Stress (Os) and Inflammationmentioning
confidence: 99%
“…Age-related hearing loss (ARHL), or presbyacusis, is a type of sensorineural hearing loss that primarily affects the elderly [1]. However, the age of onset, rate of decline, and severity of hearing loss vary widely.…”
Section: Introductionmentioning
confidence: 99%